Unsur Supranatural Dalam Teks Lamut “Kerajaan Palinggam” - Irni Cahyani (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Supernatural is above natural things, where supernatural is more aimed at natural phenomenon and is kebatinan culture / world. While the lamut is an oral literature performed by a single player (palanutan). The single player brings a certain story through the speech which in certain parts of his speech accompanied by a wasp of tarbanglamut. In this study, researchers examined the supernatural element in the text of the lamut